Production potential and Economics of hybird Rice under system of Rice intensification and its manipulation - Verma, AK; Pandey, N; Shrivastava, GK (SAARC Journal of Agriculture, 2015)
The study was conducted at Indira Gandhi Krishi Vishwavidyalaya, Chhattisgarh (21o16´ N and 81o36´ E) during wet season of 2007-08 and 2008-09 in silty clay loam soil to assess the effects of system of rice intensification (SRI) and its manipulation involving two age of seedlings (10 and 14 days), three manuring (organic alone, inorganic alone, 50% nutrients through organic + 50% nutrients through inorganic), two weeding practices (Mechanical weeding through conoweeder and chemical weeding), two water management practices (application of 2 cm water at hairline crack development stage and cyclic submergence of 5 cm water at 3 days after disappearance of ponded water) and one local recommended practices on hybrid rice (Oryza sativa L.). The results revealed manipulated SRI (10 days aged seedlings+100% nutrients through inorganic or 50% through organic + 50% through inorganic + irrigation as per SRI) gave 13.52% higher grain yield and 16.80% higher net income over recommended practices of hybrid rice. DOI: http://dx.doi.org/10.3329/sja.v12i2.21919 SAARC J. Agri., 12(2): 71-78 (2014)